2021
DOI: 10.1186/s12883-021-02438-8
|View full text |Cite
|
Sign up to set email alerts
|

Disease duration of progression is helpful in identifying isolated bulbar palsy of amyotrophic lateral sclerosis

Abstract: Background Compared with typical bulbar onset amyotrophic lateral sclerosis (ALS), isolated bulbar palsy (IBP), an often under-understood variant of ALS, is characterized by symptoms confined to bulbar region for extended periods and relative preservation of limb and ventilation function. To find a cutoff value of disease duration that can distinguish IBP from typical bulbar onset ALS well, the association of survival with disease progression in bulbar onset ALS patients was analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, limb-onset ALS accounts for two-thirds of all ALS cases, 1 and the median time from onset to significant limb weakness in bulbar-onset ALS is approximately nine months. 31 Furthermore, the MRC scale has been shown to be as good of a predictor of disease progression as forced vital capacity and ALSFRS-R, and the mBI is also strongly correlated with the ALSFRS-R. 32,33 In conclusion, we found that ALS patients face increased risk of ischemic stroke compared with controls, although the risk did not differ by the presence of disability in ALS patients. Further investigations are needed to elucidate the pathomechanism and potential risk factors of the increased risk of ischemic stroke in ALS.…”
Section: Discussionmentioning
confidence: 60%
“…However, limb-onset ALS accounts for two-thirds of all ALS cases, 1 and the median time from onset to significant limb weakness in bulbar-onset ALS is approximately nine months. 31 Furthermore, the MRC scale has been shown to be as good of a predictor of disease progression as forced vital capacity and ALSFRS-R, and the mBI is also strongly correlated with the ALSFRS-R. 32,33 In conclusion, we found that ALS patients face increased risk of ischemic stroke compared with controls, although the risk did not differ by the presence of disability in ALS patients. Further investigations are needed to elucidate the pathomechanism and potential risk factors of the increased risk of ischemic stroke in ALS.…”
Section: Discussionmentioning
confidence: 60%
“…When we examined differences in utilization for each intervention according to provider type, we found that women underwent feeding tube placement far more often than men, when a neurologist provided care, possibly due to greater prevalence of bulbar onset ALS in women than men [ 37 , 38 ]. Black beneficiaries received riluzole prescriptions and NIV less frequently than non-Hispanic White patients, despite studies suggesting that Black patients have lower baseline vital capacity and lower baseline functional scores than non-Hispanic White patients at first clinic visit for ALS [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in demographic and clinical features were compared between the patients with FLS and the patients with typical lower limb onset ALS by SPSS 18.0 software for Windows (SPSS Inc., Chicago, IL, USA). The quantitative data that were normally distributed were expressed as mean ± standard deviations (SDs), and quantitative data that were non-normally distributed were expressed as the medians and ranges (minimums, maximums) ( 12 ). The differences in categorical variables were analyzed by χ 2 test or Fisher's exact test, and continuous variables were evaluated by an independent-sample t -test or the Mann–Whitney U -test depending on the parametric or non-parametric nature of the data ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative data that were normally distributed were expressed as mean ± standard deviations (SDs), and quantitative data that were non-normally distributed were expressed as the medians and ranges (minimums, maximums) ( 12 ). The differences in categorical variables were analyzed by χ 2 test or Fisher's exact test, and continuous variables were evaluated by an independent-sample t -test or the Mann–Whitney U -test depending on the parametric or non-parametric nature of the data ( 12 ). The differences in survival between the two groups were compared using Kaplan–Meier analysis and the log-rank test.…”
Section: Methodsmentioning
confidence: 99%